Implementation of STEAM-Based Project-Based Learning to Improve Critical Thinking Skills to Support SDG 4 - Valencia Fidelia Soetra; Dwikoranto Dwikoranto; Lindsay N. Bergsma (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: The purpose of this study is to analyze the Implementation of STEAM-Based Project Based Learning to Improve Students' Critical Thinking Skills in High School. Method: The method used is a literature review which is included in qualitative descriptive research, with the population used in writing this article being several sources of articles from various accredited national and international journals. Results: Based on some of the literature that has been reviewed, the application of the STEAM-based Project Based Learning model is very effective to be applied to education in Indonesia because learning is not only centered on the teacher, but students also play an active role in learning activities. This learning model can also improve problem solving skills well. This learning model can also be used with various learning media. Novelty: The integration of STEAM and Project-Based Learning to improve the critical thinking skills of high school students in Indonesia provides a valuable gap in its effectiveness for the development of the 21st-century curriculum, while also supporting the achievement of Sustainable Development Goal 4 (Quality Education) by promoting inclusive, equitable, and future-oriented learning practices.